2013
DOI: 10.1097/mou.0b013e32835af286
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of minimally invasive versus open lymphadenectomy in urological cancers

Abstract: Findings from the prior year suggest that - in high-volume centers - lymph node dissection for urologic cancers is equivalent between open and minimally invasive techniques in lymph node yield and short-term to medium-term oncologic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…It might be derived from a large portion of robot-assisted laparoscopic RP (RARP) in our study population (32/96, 33.3%, Table 1). As known by previous studies 24-26, the rate of PLND was significantly lower in RARP than open RP (17% vs. 83% for laparoscopic RP/RARP vs. open RP, respectively, p<0.001) 25. In addition, due to the small number of patients, significant differences could not be discerned according to the adjuvant therapy strategies between the two groups (Table 1).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It might be derived from a large portion of robot-assisted laparoscopic RP (RARP) in our study population (32/96, 33.3%, Table 1). As known by previous studies 24-26, the rate of PLND was significantly lower in RARP than open RP (17% vs. 83% for laparoscopic RP/RARP vs. open RP, respectively, p<0.001) 25. In addition, due to the small number of patients, significant differences could not be discerned according to the adjuvant therapy strategies between the two groups (Table 1).…”
Section: Discussionmentioning
confidence: 67%
“…A previous systematic review and meta-analysis showed a significant difference in BCR between ePLND and sPLND in PCa patients; thus, ePLND could be an oncological benefit 23. Also, the rate of PLND was relatively lower than other studies 24-26. It might be derived from a large portion of robot-assisted laparoscopic RP (RARP) in our study population (32/96, 33.3%, Table 1).…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, achieving a high level of precision is crucial when performing template-based lymphadenectomy, particularly due to the complex surgical field surrounding the great vessels. Robotic systems offer increased control and greater dexterity, enabling more precise removal of lymph nodes, a higher number of resected lymph nodes, and a lower risk of complications ( 56 , 69 , 70 ). A study conducted by Clements et al in 2018 revealed that the use of the robotic-assisted approaches increases the probability of successful lymphadenectomy, which itself is a predictor of improved survival ( 71 ).…”
Section: Ral-nu: the Presentmentioning
confidence: 99%
“…The main role of lymph node dissection is to decrease or even better eradicate the risk of recurrence [1]. Furthermore, lymph node dissection may also provide more information about disease staging or it may lead to the early recognition of lymph node metastases, offering the opportunity to the patient to start earlier the adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%